2008
DOI: 10.1073/pnas.0810097105
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous induction of murine pancreatic intraepithelial neoplasia (mPanIN) by acinar cell targeting of oncogenic Kras in adult mice

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is believed to arise through a multistep model comprised of putative precursor lesions known as pancreatic intraepithelial neoplasia (PanIN). Recent genetically engineered mouse models of PDAC demonstrate a comparable morphologic spectrum of murine PanIN (mPanIN) lesions. The histogenesis of PanIN and PDAC in both mice and men remains controversial. The most faithful genetic models activate an oncogenic Kras G12D knockin allele within the pdx1-or ptf1a/p48-expression dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
327
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(360 citation statements)
references
References 35 publications
18
327
3
1
Order By: Relevance
“…The identity of the cell types capable of giving rise to pancreatic cancer is an area of active investigation and considerable debate (Guerra et al 2007;Habbe et al 2008;Gidekel Friedlander et al 2009;Kopp et al 2012;Puri et al 2015). The Adeno-Cre and Lenti-Cre that we used in this study mostly had ubiquitous promoters (CMV and PGK, respectively), which led to recombination in acinar, ductal, and islet cells in the pancreas, although Lenti- Cre had a very strong preference for acinar cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the cell types capable of giving rise to pancreatic cancer is an area of active investigation and considerable debate (Guerra et al 2007;Habbe et al 2008;Gidekel Friedlander et al 2009;Kopp et al 2012;Puri et al 2015). The Adeno-Cre and Lenti-Cre that we used in this study mostly had ubiquitous promoters (CMV and PGK, respectively), which led to recombination in acinar, ductal, and islet cells in the pancreas, although Lenti- Cre had a very strong preference for acinar cells (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4B). While a vast majority of pancreatic cancer studies have used non-cell type-specific promoters to drive Cre, models using transgenic and knock-in Cre(ER) alleles to enable cell type-specific expression of oncogenic Kras and tumor suppressor loss have been used to identify cells that possess the ability to give rise to PDAC (Guerra et al 2007;Habbe et al 2008;Gidekel Friedlander et al 2009;Kopp et al 2012;Puri et al 2015). However, comprehensive studies that target diverse genomic alterations to a greater array of defined cell types are simply not feasible using current transgene-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…These observations supported suggestions that acinar-to-ductal metaplasia could develop within acinar cell carcinomas. 5 Subsequent to that study, we 6 and other workers 7,8 demonstrated that acinar cell targeted expression of mutant Kras caused acinar-to-ductal metaplasia in non-neoplastic pancreas, leading to preneoplastic pancreatic intraductal neoplastia. Cells lining these structures display morphological features of ductal epithelium.…”
mentioning
confidence: 89%
“…Nevertheless, recent studies report that at least a part of pancreatic carcinoma may originate from acinar or centro-acinar cells or develop in specialized pancreatic compartments, represented by the gland-like mucinous outpouches of major ducts. 55,56 In particular, available experimental evidence seems to suggest that, in a context of persistent inflammation in pancreatic tissue, a process characterized by acinar-to-ductal mucinous metaplasia may occur. Furthermore, in this organ, human acinar cells adjacent to areas of cancer present ductal markers.…”
Section: Pancreatic Carcinoma Cytogenesis and Histogenesismentioning
confidence: 99%